Unfolding The Action Through Process Types: A Corpus- Based Comparative Analysis Of Native And Pakistani English Short Stories - Muhammad Ansar Ejaz , Professor Dr. Muhammad Asim Mahmood (corresponding Author) , Dr. Ayesha Asghar Gill (Migration Letters, 2024)
Process Types a key component of Hallidayan (2014) transitivity model are the lexemes used to depict the unfolding of action while presentation of experiential perspective in some narrative. Analysis of the process types in a narrative provides a comprehensive picture of the nature of the text and comprehension of the experiential perspective presented by the author. The current study has analyzed the corpus of three Native English and three Pakistani English short stories to explore the role of Process types for the presentation of experiential perspective. The corpus were tagged for transitivity analysis through The UAM Corpus tool and interpreted in accordance with the Hallidayan model of transitivity (2014). The results show that Native English writers are more concrete and tangible in their approaches for the presentation of experiential perspective using vivid and tangible storytelling approaches that engage readers in the narrative world. Contrarily non-native Pakistani writers take a more abstract and philosophical approach to delve into deeper themes and ideas for presentation of experiential perspective. Native English writer focus more on reasoning and logic for the development of the narrative compared to Pakistani writers who p1rioritize details and descriptions. Native English writers focus on visible and observable behaviours whereas Pakistani writers delve deep into the psychological states of the participants for the presentation of experiential perspective. Native writers are straightforward and direct while unfolding the action compared to Pakistani writers who indirectly approach the presentation of unfolding of action. The results will be helpful for classroom as well as research domain.